RISK FACTORS FOR URINARY BLADDER CANCER IN BALUCHISTAN - Ahmad, Muhammad Riaz; Pervaiz, Muhammad Khalid; Chawala, Javed Akhtar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Urinary Bladder cancer is a life threatening and aggressive disease. This retrospective study was conducted in Baluchistan for assessing the risk factors for urinary bladder cancer. Method: A questionnaire was developed in order to collect the requisite information about the characteristics like age, drinking habits, smoking history, family history of cancer and others factors. Interview method was used to obtain the information from 50 cases and 100 controls from two hospitals of the province. Binary logistic regression model was run to study the odds ratios and 95% confidence intervals. Results: The odds ratios and 95% confidence intervals for cigarette smoking, fluid consumption and higher use of fruits were [26.064; 7.645-88.856], [0.161; 0.059- 0.441], and [0.206; 0.059-0.725] respectively. Conclusions: The higher risk of urinary bladder cancer was observed in smokers as compared to non-smokers. Higher consumption of fluid and fruits are protective factors against the disease. Keywords: Risk factors, Controls, Odds ratio, Questionnaire, Bladder Cancer